THE ANALYSIS OF NURSERY RHYMES AS ORAL TRADITION IN MAKASSAR - Andi Hajar (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
Nursery rhymes is one of oral tradition that exist in all of the cultures like in Makassar, South Sulawesi. The purpose of nursery rhymes are to educate and entertain the small children. The songs can be identified in three forms: songs only, songs that are sung while playing games, and lullaby songs intended for babies and small children. We can find many songs that exist for years, like Bintang Kecil, Kasih Ibu, Pelangi-Pelangi, Burung Kakatua, Topi Saya Bundar, etc. The kinds of songs that sung while playing games in Makassar are Cincin banca, Domikado, Lojo’-Lojo’, Tumbu’-Tumbu’ Blanga, Ular Naga, etc. Lullaby songs are Nina Bobo, and some local songs like Yabe Lale, Alama Sea-Sea, Labuni Essoe, O indokku… O Ambokku. Children creativity also develop when they are playing. They create different version of the songs. Nursery rhymes also has important roles and some benefits for the children like improving their speaking skills, improving their language, vocabularies, and sentence structure that are easy to be learned by the children. Also nursery rhymes have benefits to strengthen their physic like running, jumping, etc. The last, playing and singing can improve the togetherness and solidarity among children.